Contemporary National Security of India: Puzzles and Policy Options - Nandy, Debasish; Saifuzzaman, Saifuzzaman; Patra, Anupam; Besra, Ananta Kumar (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2025)
The study argues that India’s national security has faced significant challenges over the years, both domestic and foreign. The socio-political landscape plays a crucial role in shaping the dynamics of internal security. Separatist movements, as well as radical political and religious ideologies, have emerged as major threats to national stability. On the other hand, suspicious actions by neighboring countries have raised concerns about India’s external security. In addition to maintaining territorial integrity, India is also concerned about maritime security and potential nuclear threats from parties considered as strategic adversaries. The study also examines non-traditional security threats and how the Indian government has responded to these challenges through various security policies and strategic alliances with other countries. Given the increasingly complex and evolving challenges, an integrated approach is needed across the three main branches of India’s defense. In addition, the study will discuss the ongoing security tensions between India and Bangladesh, and the role of China and Pakistan in exacerbating bilateral security issues. The study uses content analysis as the primary approach in examining the dynamics of India’s security as a whole.